UTILIZATION OF GABUS PASIR(BUTIS AMBOINENSIS) WASTE FISH MEAL FOR SUBSTITUTION OF COMMERCIAL FISH MEAL IN DIET ON FERTILITY, HATCHABILITY AND EMBRYO MORTALITY OF EGG LAYING DUCK - Dian Syahputra (Universitas Sumatera Utara, 2016)
This research was conducted at Laboratory Animal Biology, Agriculture Faculty, Sumatera UtaraUniversity from March to July 2015. This study aimed to determine the effect of gabus pasir waste fish meal(GPWFM)(Butis amboinensi) in diet of laying duck on fertility, hatchability and embryo mortality of duck egg. The design used in this research was completely randomized design (CRD) with 3 treatments and 6 replications. The treatment consisted of level substitution GPWFM by commercial fish meal at ratio 0:10 (P0); 5:5 (P1); and 10:0 (P2). This research used 134 eggs from 52 ducks and 18 drakes. The results showed the average offertility percentage on treatment such as: 97,92; 100 and 100,respectively, hatchability (%) such as: 76,63; 79,50and 84,17, respectively and embryo mortality (%) such as:23,37; 20,45 and 15,83, respectively. The results analys showed that the treatmentshad no significantly on fertility, hatchability and embryo mortality (P>0,05), The conclusion of this research that gabus pasir waste fish meal can substitution of commercial fish meal. Keywords: Gabus pasir waste fish meal, fertility, hatchability and embryo mortality of egg laying duck